Predictors in late adolescent college students' attitudes towards police and their attitudes towards parents, teachers, and police as a function of self-esteem - Smith, Kathleen Dee (1995)
Probably one of the biggest concerns today of most Americans is the problem of crime. Police depend heavily upon citizens to help them fight crime, and so attitudes toward police are important since it is these attitudes which can directly help or hinder police effectiveness. Adolescents are over-represented in committing crimes; therefore, they become a target group in establishing positive community-police relations. Attitudes towards the self are equally important since how we feel about ourselves influences our attitudes towards others. This research investigated the variables of sex, race, age, city size, socioeconomic status, delinquency, police contact, and self-esteem to determine their importance in predicting late adolescents' attitudes toward police. It also studied the relationship between self-esteem and attitudes toward parents, teachers, and police. Subjects were 448 late adolescent college students drawn from two Midwestern universities who completed an in-depth questionnaire. Multiple regression, path analysis, and correlational analyses were the statistical procedures used. Results showed that delinquency was the best predictor in attitudes toward police, followed by self-esteem and then race. These were the only variables that achieved significance. All of the tested variables combined explained 13% of the total variance in attitudes toward police. Results further indicated that the more these late adolescents liked themselves, the more they liked their mothers, their teachers, and police, in that order. There was some support that this relationship may also hold true regarding attitudes toward fathers. Limitations of the study are discussed as well as directions for future research and policy recommendations